Analysis of Clothes of Persons With Disability with Palsy Cerebral for Adolescents Based on Topography - Putri, Vera Utami Gede; Prabawati, Melly; Noerharyono, M (Fakultas Pariwisata dan Perhotelan Universitas Negeri Padang, 2023)
This study aims to determine needs about form of clothing for disabled people with cerebral palsy for young women. The research was conducted at Development Foundation for Children with Disabilities, Jakarta. 5 respondents with disabilities were grouped into 2 group based on topography or the number of disabilities in their bodies. The research method used is qualitative with a case study research approach. The result of this study indicates the need for dress form according to the conditions of type of disability based on the topography, namely diplegia and triplegia. Respondents still need help from others in dressing; experiencing difficulties in dressing; comfort and like the position of the front opening; can use types of openings such as zippers, buttons, and velcro; having difficulty with eye and hand coordination so it is more comfortable to use buttons that are not too small such as medium size buttons with less buttons. Respondents use pants for their daily clothes; baggy pants size maxi, midi and angkel size. The type of materials used are materials that fall, not too stiff and cool, colors suitable for adolescents can be dark but not black so they are not easily dirty, comfortable and prefer looser clothes; comfortable wearing more closed clothes; comfortable using thin cotton. On average, respondents having no problem in choosing colors on clothes, but rather on models and openings that need special creation based on topographic types.